Optimization Design of Pure Electric Vehicle Power System Speed Ratio - Jintang Zheng; Jiqing Chen (Jixie chuandong)
Comprehensive consideration of the dynamic performance， driving range and energy consumption requirements of pure electric vehicles， on the basis of a fixed speed ratio pure electric vehicle as the research sample， in order to make the driving motor work point on the high efficiency area， two-speed Automatic Manual Transmission (AMT) drive scheme is put forward. The mathematical model of two gears AMT pure electric vehicle model and power system optimization model are established on Cruise simulation platform. Based on the Isight integration Cruise， the co-simulation process and platform of AMT pure electric vehicles are constructed. With 100 km/h acceleration time and the NEDC working condition per 100 km energy consumption as the optimization objectives， the maximum speed， the maximum climbable gradient and speed ratio constraint are used as constraints， the speed ratio of the powertrain are optimized， after optimization of the design variables， the reference two-parameter shift strategy in speed and load degree are established， in the meanwhile， a simulation research is conducted on the dynamic and economic performance of the vehicle with Cruise. The results show that， the NEDC consumption has reduced by 0.52 kWh/100km， the economic improvement rate is 3.78%， and the 100 km/h acceleration time has shortened by 2.23%.